Crainte, jalousie, indignation, espoir… ou le chemin vers la reconnaissance des écrivains immigrants au Québec - Mouneimné, Tina (Romanica Silesiana)
This article aims at browsing the reasons why French-speaking authors of ethnic origin had to “fight” for their place in the Quebec literary pantheon and how they have succeeded in doing it. The battle for the recognition of the immigrant writer has proceeded in parallel to the battle fought in the name of recognition of the immigrant himself in the society. It was, in fact, due not only to the outstanding quality of some of these francophone authors’ works, but also to the socio-political circumstances related to the changes occurring in Quebec since the 1960’s. However, as it has been underlined through the “Affaire LaRue”, the only criteria of recognition of anyone’s text should be the quality of their work, otherwise, we fall into other, endless discourses concerning identity, immigration policies, etc. that take us away from literature. Key words: Literature, Quebec, immigrant, LaRue, recognition.